2016
DOI: 10.1088/1361-6560/61/24/8890
|View full text |Cite
|
Sign up to set email alerts
|

Monte Carlo studies on water and LiF cavity properties for dose-reporting quantities when using x-ray and brachytherapy sources

Abstract: Model-based dose calculation algorithms (MBDCAs) are the current tools to estimate dose in brachytherapy, which takes into account heterogeneous medium, therefore, departing from water-based formalism (TG-43). One aspect associated to MBCDA is the choice of dose specification medium since it offers two possibilities to report dose: (a) dose to medium in medium, D ; and (b) dose to water in medium, D. The discussion about the preferable quantity to be reported is underway. The dose conversion factors, DCF, betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 28 publications
0
2
0
2
Order By: Relevance
“…The denominator in the above equation was calculated using MC simulation in a previous work (Moutsatsos et al 2014) and found equal to 1.231 ± 0.56%. The numerator was obtained from MC simulations of this work that accounted for the geometry and physical properties of both the TLDs and the phantom in the experimental irradiation (see section 2.6) under the large cavity assumption (Branco et al 2016). k bq accounts for the difference in the relation between detector reading and dose to the detector in the experimental ( 192 Ir) and calibration (6 MV) irradiations.…”
Section: Point Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…The denominator in the above equation was calculated using MC simulation in a previous work (Moutsatsos et al 2014) and found equal to 1.231 ± 0.56%. The numerator was obtained from MC simulations of this work that accounted for the geometry and physical properties of both the TLDs and the phantom in the experimental irradiation (see section 2.6) under the large cavity assumption (Branco et al 2016). k bq accounts for the difference in the relation between detector reading and dose to the detector in the experimental ( 192 Ir) and calibration (6 MV) irradiations.…”
Section: Point Measurementsmentioning
confidence: 99%
“…Additional MC simulations were performed in order to support experimental dosimetry. Dose to TLD in PMMA required for the calculation of the TLD relative absorbed dose energy dependence according to equation (3) was estimated by scoring collision KERMA in PMMA using rectangular * FMESH4 tallies (Branco et al 2016) superimposed over the axial lattice slices including the TLDs. The resolution of each * FMESH4 tally coincided with the lattice resolution (1.37 × 1.37 × 1 mm 3 ).…”
Section: Dose Calculationsmentioning
confidence: 99%
“…Em braquiterapia, tal conversão é um pouco mais complexa, já que dependendo da fonte utilizada a cavidade pode se comportar como pequena, média ou grande em relação ao alcance dos elétrons secundários 79 . Em geral, para fontes que emitem fótons com energia abaixo de 50 keV, como as avaliadas neste trabalho, o alcance dos elétrons é comparado às dimensões das células (alguns µm) 14 , de forma que a cavidade pode ser considerada grande e a dose absorvida proveniente da energia depositada pelas partículas carregadas dentro da d Poder de freamento (stopping-power): representa a perda média de energia por unidade de caminho em um determinado meio de densidade  , devido à colisões Coulombianas com elétrons atômicos.…”
Section: Revisão Da Literatura | 21unclassified
“…As dimensões das células mamárias, por exemplo, são de aproximadamente 10 µm, o que faz com que tais cavidades sejam consideradas pequenas quando irradiadas com fontes de braquiterapia de energia alta, e grandes quando irradiadas com fontes de braquiterapia de energia baixa. Fatores como estes tornam a metodologia de conversão entre as doses o objeto de estudo para muitos pesquisadores 18,23,79,82 .…”
Section: Revisão Da Literatura | 23unclassified